2007
DOI: 10.1161/hypertensionaha.107.093260
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Hypercholesterolemia Differentially Affect the Function and Structure of Pig Carotid Artery

Abstract: Abstract-The purpose of this work was to compare the effects of hypertension and hypercholesterolemia on carotid endothelial function, structure, and vasa vasorum density. Seventeen pigs were randomized to a 12-week normal diet without (nϭ5), or with renovascular hypertension (HT; nϭ6), or to a high cholesterol diet (HC; nϭ6). Carotid arteries were studied by organ chambers (endothelial function) and microcomputed tomography (vasa vasorum), and tissue was processed for Sirius red staining and immunoblotting (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Comparing our finding of more thinner (green) collagen fibers at 5 or 8 weeks to the finding by Versari et al [41] of more thicker (red/orange) collagen fibers in porcine carotid arteries at 12 weeks post-surgery in a renovascular model of hypertension suggests that the “maturation” of collagen fibers may take longer than basic geometric changes (cf. [21]).…”
Section: Discussionsupporting
confidence: 83%
“…Comparing our finding of more thinner (green) collagen fibers at 5 or 8 weeks to the finding by Versari et al [41] of more thicker (red/orange) collagen fibers in porcine carotid arteries at 12 weeks post-surgery in a renovascular model of hypertension suggests that the “maturation” of collagen fibers may take longer than basic geometric changes (cf. [21]).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to the results of a prior study using a renovascular hypertensive swine model which showed that carotid IMT became greater at 3 months. 11 These results indicate that 3 to 4 months of induced hypertension is associated with fibrosis, vascular wall thickening, and carotid plaque development, which might impair endothelium-independent vasorelaxation and vasa vasorum growth leading to carotid plaque development. 11 From the 8th to the 12th month in the current study, the plaque scores in the constriction group were all significantly higher than in the sham group, and 12 months after clip placement carotid plaque formation was proven by digital subtraction angiography and histological examination.…”
Section: Discussionmentioning
confidence: 69%
“…11 These results indicate that 3 to 4 months of induced hypertension is associated with fibrosis, vascular wall thickening, and carotid plaque development, which might impair endothelium-independent vasorelaxation and vasa vasorum growth leading to carotid plaque development. 11 From the 8th to the 12th month in the current study, the plaque scores in the constriction group were all significantly higher than in the sham group, and 12 months after clip placement carotid plaque formation was proven by digital subtraction angiography and histological examination. Also in the present study, biochemical parameters were not different between the groups at the indicated time points, suggesting that the plaque formation was not caused by chronic elevation of these factors.…”
Section: Discussionmentioning
confidence: 69%
“…Versari et al [37] in experimental research in an animal model confirmed a different influence of hypercholesterolemia and hypertension on the structural and functional changes of the carotid arteries. They found that both risk factors induced an increase in systemic and vascular oxidative stress, with a consequent reduction in vasorelaxation.…”
Section: The Effect Of Arterial Hypertension and Hypercholesterolemiamentioning
confidence: 84%